PTU-087 Developing Models of Engagement in a New Migrant Population: Results from a Large Scale Hepatitis B & C Testing Study in the UK Nepali Community. (17th August 2016) - Mathew, S; Petrova, M; Hendy, J; Van Vlymen, J; Jones, S; de Lusignan, S; Zamani, J; Pilcher, A; Tiwari, R; Nicholls, M; Ala, A; Ala, A
Abstract : Introduction: The UK Nepali community has grown by over 900% since 2004, when settlement rights were introduced for ex-Gurkha servicemen and their dependants. Nepal sits between India and China; two countries with higher rates of hepatitis B & C, but rates in the UK Nepali population is unknown Methods: The Nepali community has multiple castes and religious beliefs. Little is known about disease and healthcare perception, and focus group sessions were held before testing. National ethics approval was obtained, and testing sessions were held in community venues centrally located to known population clusters in Surrey, UK. Study advertising was limited to existing Nepali language media and word of mouth, following concerns raised by the activity of far right groups. Fingerprick testing was used, with community leaders helping to facilitate testing. Questionnaires were used for possible risk associations including: blood transfusions, surgery, and place of origin. Results: 1005 Nepali individuals (age > 18 yrs, Male = 45%) were tested over 17 sessions from Mar 2013 - Jan 2015. A total of 973 individuals were included in final analysis (mean age 63 yrs, range 19–86). Median length of stay in the UK was 36 months, with 18 individuals (1.8%) present in the UK for more than 10 years HBsAg was detected in 3 (0.31%) and HCVAb in 4 (0.41%) separate individuals; showing low rates of infection. HBsAg patients had absent or low level HBV DNA (<300iu/ml), and all HCV patients were RNA negative, with no evidence of cirrhosis in attending patients on follow-up (5/7). Hepatitis B core Ab (HBcAb) was detected in 93 individuals (9.6%), mean age 67 yrs (22–84 yrs) Regression analysis showed no statistical associations with HBsAg / HCVAb presence; but HBcAb was significantly associated with male gender and fewer years spent at school (p = 0.002 and p = 0.02 respectively) Conclusion: Rates of active CVH were very low in the Nepali community, but with higher rates of previous HBV exposure, which may have implications for ongoing testing programmes. Given the absence of a common religious or cultural forum to target this new community, we used detailed focus group sessions and developed strong community links to produce a successful community-based approach to engagement, which we hope will act as a model of testing in other communities. Disclosure of Interest: None Declared